Mock-Ups: Using Experiential Simulation Models in the Healthcare Design Process. (April 2019) - Durham, Joyce; Kenyon, Ann
Purpose: The purpose of this article was to explore how different types of mock-ups are being used in the healthcare design process and present a methodology framework for the process. Background: Historically, physical mock-ups have been used in healthcare design primarily to test construction techniques. Although this historic use of mock-ups assisted the design team in decision-making, newer forms of mock-ups have evolved that expand the input provided into decision-making. These newer techniques, rapid prototyping, early build-out, virtual reality, and enhancements to the traditional physical mock-up focus more on challenging the functionality of the space, testing new operational concepts, and increasing user input. Method: This methodology article utilized five case studies in which different types and combinations of mock-ups were used in the design process and then, the methodology compares the realism, immersion, and testability of each mock-up technique. Results: For each mock-up type, the case studies described the purpose of the technique, the advantages and disadvantages, the most appropriate phase for its use in the design process, the estimated cost, and the process logistics. These components are compared to assist in developing a methodology for a variety of design situations. Conclusions: The findings related to different mock-up techniques are a valuable tool for healthcare design teams to use in selecting the most appropriate mock-up technique and the proposed methodology will assist in executing the mock-up process.